ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล ความฉลาดทางอารมณ์ บรรยากาศองค์การ และพฤติกรรมความร่วมมือในการปฏิบัติงานของพยาบาลประจำการ หน่วยอภิบาลผู้ป่วยหนัก โรงพยาบาลมหาวิทยาลัยของรัฐ - ธนิษฐา สมัย (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of this research were to study cooperative working behavior of staff nurses in intensive care units, governmental university hospitals, and to investigate the relationships between personal factors, emotional quotient, organizational climate and cooperative working behavior of staff nurses in intensive care units, governmental university hospital. The subjects consisted of 285 staff nurses selected by multi-stage sampling. Research instruments were emotional quotient, organizational climate and cooperative working behavior questionnaires, which were tested for content validity and reliability. Cronbach s alpha coefficients were .93 .86 and .93, respectively. Statistical methods used for data analysis included mean, standard deviation, and Pearson s product moment correlation. Major findings were as follows: 1. Mean scores of cooperative working behavior of staff nurses in intensive care units, governmental university hospitals was at the high level (x = 3.82), emotional quotient was at the normal level (raw score = 164.61), and organizational climate was at the middle level (x = 3.43). 2. Age, educational level, and work experience were not significantly related to cooperative working behavior of staff nurses in intensive care units, governmental university hospitals. 3. Emotional quotient and organizational climate were positively and significantly related to cooperative working behavior of staff nurses in intensive care unit (r = .406 and .552 p< .05).